Cache coherency controller for MESI protocol based on FPGA - Mays K. Faeq; Safaa S. Omran (International Journal of Electrical and Computer Engineering (IJECE), 2021)
In modern techniques of building processors, manufactures using more than one processor in the integrated circuit (chip) and each processor called a core. The new chips of processors called a multi-core processor. This new design makes the processors to work simultanously for more than one job or all the cores working in parallel for the same job. All cores are similar in their design, and each core has its own cache memory, while all cores shares the same main memory. So if one core requestes a block of data from main memory to its cache, there should be a protocol to declare the situation of this block in the main memory and other cores.This is called the cache coherency or cache consistency of multi-core. In this paper a special circuit is designed using very high speed integrated circuit hardware description language (VHDL) coding and implemented using ISE Xilinx software. The protocol used in this design is the modified, exclusive, shared and invalid (MESI) protocol. Test results were taken by using test bench, and showed all the states of the protocol are working correctly.